Optimal placement, sizing and power factor of distributed generation: A comprehensive study spanning from the planning stage to the operation stage - Huy P.D.; Ramachandaramurthy V.K.; Yong J.Y.; Tan K.M.; Ekanayake J.B. (Elsevier Ltd, 2023)
Electric power factor; Electric power transmission networks; Evolutionary algorithms; Optimization; Differential Evolution; Differential evolution algorithms; Distributed generation source; Multiple distributed generations; Optimal allocation; Optimisations; Power factorAbstract; Power system constraints; Distributed power generation; algorithm; distribution system; energy planning; operations technology; optimization